Osmium isotopes in Baffin Island and West Greenland picrites: implications for the 187 Os/ 188 Os composition of the convecting mantle and the nature of high 3 He/ 4 He mantle - Dale, C.W.; Pearson, D.G.; Starkey, N.; Stuart, F.M.; Ellam, R.M.; Larsen, L.M.; Fitton, J.G.; Macpherson, C.G. (Earth and Planetary Science Letters, 2009)
Identifying the Os isotope composition of the prevalent, largely peridotitic, convecting mantle places important constraints on the Earth's accretion, differentiation and evolution and also has implications for the interpretation of Re-depletion ages in mantle peridotites. As partial melting preferentially samples mantle components with the lowest melting temperatures, large degree melts such as picrites should most closely reflect the peridotitic components within the source. Thus, Re–Os analyses of thirty picrites from Baffin Island and West Greenland are thought to provide a good estimate of the bulk 187 Os/ 188 Os composition of their convecting mantle source, which is indistinguishable from DMM in terms of lithophile isotopes and trace elements. In addition, the high 3 He/ 4 He of these rocks allows us to comment on the possible origins of high 3 He/ 4 He mantle. Ingrowth-corrected 187 Os/ 188 Os of the picrites ranges from 0.1267 to 0.1322. The higher 187 Os/ 188 Os samples have correspondingly lower 143 Nd/ 144 Nd which can be explained by contribution (~ 5%) from old recycled oceanic crust, including sediment. However, Baffin Island and the earliest West Greenland picrites are remarkably uniform in composition with 187Os/188Os between 0.1267 and 0.1280, and a mean and mode of 0.1272 ± 0.0007. Such Os isotope compositions are less radiogenic than estimates of primitive upper mantle but are similar to the least radiogenic mid-ocean ridge basalts (MORB) and the most common composition of ophiolite-derived platinum-group alloys and chromites. These compositions appear to represent a source dominated by peridotite. The picrites studied record the highest known 3 He/ 4 He in the silicate Earth (up to 50 Ra). For this signature to reflect isolated domains of ancient melt depletion would require significantly less radiogenic Os isotope compositions than observed ( 187 Os/ 188 Os : < 0.115), unless radiogenic Os, but not He, has been subsequently added. Conversely, a bulk outer core contribution would impart a ...